Magnetic resonance-guided laser interstitial thermal therapy vs. stereoelectroencephalography-guided radiofrequency thermocoagulation in epilepsy patients with focal cortical dysplasia: a systematic review and meta-analysis - Li, Yiming; Gao, Jiayi; Ye, Zi; Mu, Jie (Frontiers in Neurology, 2023)
Background: Magnetic resonance-guided laser interstitial thermal therapy (MRgLiTT) and stereoelectroencephalography-guided radiofrequency thermocoagulation (SEEG-RFTC) are two effective, minimally invasive treatments for epilepsy with focal cortical dysplasia (FCD). The purpose of this study is to conduct a meta-analysis to evaluate and compare the efficacy and safety of these two therapies in epilepsy patients with FCD. Methods: We searched PubMed, Embase, Cochrane and other databases for papers published before March, 2023. The primary objective was to compare the effectiveness and complications of MRgLiTT and SEEG-RFTC in epilepsy patients with FCD. The second objective was to determine which method provides better prognosis for specific subgroup patients. Results: According to the inclusion and exclusion criteria, 18 studies were included, comprising 270 FCD patients including 37 patients from 6 MRgLiTT studies and 233 from 12 SEEG-RFTC studies. There were no significant differences between MRgLiTT and SEEG-RFTC groups in the seizure-freedom rate (59%, 95%CI 44%-74%; 52%, 95%CI 47%-57%, P = 0.86) and the rate of ≥50% seizure-reduction of FCD (90%, 95% CI 80%-100%; 90%, 95%CI 86%-94%, P = 0.42). Both methods had low complication rates (17.1%, 28/159) and long-term complication (2.5%, 4/159) rate, with no significant difference between them (P = 0.17). Conclusions: Both MRgLiTT and SEEG-RFTC are safe and minimally invasive treatments for patients with FCD. They have comparable performance in terms of postoperative seizure-freedom rates in patients with FCD, and both can be used as treatment options for patients with FCD. And our study found that SEEG-RFTC had a better therapeutic effect in the FCD2b subgroup.